2021
DOI: 10.21926/rpm.2103034
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Release from Orthodontic Clear Aligners: An In-Vitro Study

Abstract: Bisphenol A (BPA) is a widely used synthetic compound that has been identified as an endocrine disruptor. It has been linked to adverse health effects such as developmental defects, infertility in both men and women, cardiovascular disease, and obesity. There has been increased interest in BPA’s effects on the developing fetus and data has revealed that doses below the presumed safe dose can produce harmful effects. Orthodontic clear aligner therapy is a popular treatment modality that involves the patient wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…However, the BPA concentration at T 0 was significantly lower in the VFR group comparatively. Katras et al (2021) reported a well-documented release of BPA at all time intervals from all the CA materials tested. It was found that the concentrations reached the peak at different time points for the different materials.…”
Section: Summary Of Evidencementioning
confidence: 82%
See 4 more Smart Citations
“…However, the BPA concentration at T 0 was significantly lower in the VFR group comparatively. Katras et al (2021) reported a well-documented release of BPA at all time intervals from all the CA materials tested. It was found that the concentrations reached the peak at different time points for the different materials.…”
Section: Summary Of Evidencementioning
confidence: 82%
“…None of the included studies provided information on sample size determination, random sequence generation and concealment mechanism, and where the full trial protocol can be accessed (Table 2). Only one study (Katras et al, 2021) reported blinding of the investigators and two (Katras et al, 2021; Schuster et al, 2004) on the inherent limitations of the study.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations